Implementation of tahfidz learning using the Tahsin and Tasmi' Methods - Yudi Darmawan; Adi Putra; Noprijon (STAI YAPTIP Simpang Empat Pasaman Barat Indonesia in collaboration with International Islamic Studies Development and Research Center (IISDRC), 2025)
Maintaining the memorization of the Qur'an is very important and difficult, therefore it is highly recommended in memorizing the Qur'an for the memorizers to use the tahfidz, tahsin and tasmi' methods continuously. In order to make it easier for them to add memorization and maintain memorization. This study aims to analyze and describe the Implementation of tahfidz tahsin and tasmi' learning in improving the quality of students' memorization of the Qur'an at Mts Darul Yamani, Kejorongan Pisang Hutan, Sasak Ranah Pasisie District, West Pasaman Regency. This study uses a field research method, the type of approach is qualitative, The source of this research data is Primary data obtained through interviews with informants, namely the Principal of MTS Darul Yamani, teachers and students of SMK Darul Yamani regarding the Implementation of tahfidz learning using the tahsin and tasmi' methods at MTS Darul Yamani. Tahfidz learning using the tahsin and tasmi' method at MTS Darul Yamani is implemented once a week so that students understand and memorize the Qur'an more quickly. The form of the method used before teaching must use a learning plan. The implementation process that the tahsin and tasmi' method in tahfidz learning is one of the lessons to support the Qur'an tahfidz program. As well as evaluation of the implementation of tahfidz learning using the tahsin and tasmi' method is that at the end of each semester, MTS Darul Yamani holds an Al-Qur'an memorization test to evaluate student achievement. Students must meet the memorization targets that have been set according to their class level and supporting factors in the implementation of tahfidz learning using the Tahsin and tasmi' method are that the tahfidz program gets full support from the school, parental encouragement and student interest in participating in tahfidz learning. The inhibiting factors are due to sin and immorality, intentions that are not sincere because of Allah SWT and being full. The implications of this research can be used as initial data for subsequent researchers in studying this problem in different contexts and issues.